Comparison of Enzyme-Linked Immunosorbent Assay and Passive Hemagglutination Method for Quantification of Antibodies to Lipopolysaccharide and Tetanus Toxoid in Rats - Vos, J. G. (1979)
In a comparative study, the enzyme-linked immunosorbent assay, using peroxidase labeled anti-rat immunoglobulin M and immunoglobulin G, and the passive hemagglutination test were applied to determine the primary and secondary antibody response to lipopolysaccharide and tetanus toxoid in rats. In the enzyme-linked immunosorbent assay, the antigens were bound to the wells of polystyrene microplates, tetanus toxoid directly, and lipopolysaccharide after complexing it with methylated bovine serum albumin. After incubation with dilutions of the rat sera, the amount of antibody bound to the solid phase was quantified by means of peroxidase-labeled anti-immunoglobulin. The specificity of the enzyme immunoassay was tested by absorption of the sera with their respective antigens. The enzyme-linked immunosorbent assay proved to be more sensitive than the hemagglutination reaction, except when titers were determined during the secondary response to tetanus toxoid. Besides its specificity and sensitivity, the enzyme-linked immunosorbent assay is a convenient method for measuring both immunoglobulin M and immunoglobulin G antibodies. At low serum dilutions of lipopolysaccharide antisera, inhibition of the reaction in the enzyme-linked immunosorbent assay occurred. This phenomenon could be prevented by heating the sera at 56°C for 30 min. Lipopolysaccharide was immunogenic in rats over an extremely wide dose range (from 10 pg to 1 mg); the optimal immunogenic dose of lipopolysaccharide for young adult rats was 0.1 to 1,000 μg when administered intravenously, and that of tetanus toxoid was 5 to 10 lines of flocculation, as determined by the Ramon flocculation test.